2022
DOI: 10.17306/j.jard.2022.01558
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of market margins among okra traders

Abstract: In the tropics, okra is an important vegetable crop and its production is a viable livelihood activity; however, several factors affect its marketing and margins derivable thereof. Therefore, this study analyzed the determinants of market margins among okra traders in Owerri, Imo State, Nigeria. Primary data collected via multistage sampling were analyzed using descriptive statistics, market performance and regression analysis. The results revealed that the estimated market margin and market efficiency index w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 7 publications
3
3
0
Order By: Relevance
“…This factor is influenced by the forces of demand and supply, which are determinants of market equilibrium. This result aligns with the findings of Onuwa et al (2022) and Ugwumba (2009), who similarly observed a significant and positive correlation between the sales volume of agricultural commodities and the marketing margin of the participants in their respective studies on agro-commodity marketing.…”
Section: Determinants Of Marketing Marginsupporting
confidence: 91%
See 3 more Smart Citations
“…This factor is influenced by the forces of demand and supply, which are determinants of market equilibrium. This result aligns with the findings of Onuwa et al (2022) and Ugwumba (2009), who similarly observed a significant and positive correlation between the sales volume of agricultural commodities and the marketing margin of the participants in their respective studies on agro-commodity marketing.…”
Section: Determinants Of Marketing Marginsupporting
confidence: 91%
“…Other constraints include the perishability of the commodity (45.2%), inadequate storage facilities (44.2%), price volatility (38.9%) and exploitation by middlemen/agents (24.2%). This is consistent with findings from Onuwa et al (2022), Slamet et al (2017), Asa et al (2012) and Sreenivasa et al (2007), who also highlighted [in their respective studies] similar constraints that significantly impacted agro-commodity marketing.…”
Section: Constraints Of African Aubergine Marketingsupporting
confidence: 89%
See 2 more Smart Citations
“…Thus, the amount of years the respondents spent in the marketing function has a direct impact on their marketing experience; and as such, improving agricultural produce marketing effectiveness over a period of time. This finding is supported by (Onuwa et al, 2022;Onuwa et al, 2017) who posited related findings on profitability of agricultural produce marketing.…”
Section: Determinants Of Market Marginmentioning
confidence: 57%